A modified low-carbon cement and preparation method thereof
Through the combination of low-calcium silicate cement clinker, silicon-aluminum additives and composite treatment agents, the problem of insufficient early strength of low-carbohydrate cement is solved, efficient grinding and early strength improvement are achieved, and desert sand and coal gangue resources are utilized. Reduces production costs and has significant economic and environmental benefits.
Patent Information
- Application Number
- CN202310823011.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-06
AI Technical Summary
The existing low-carb cement is difficult to effectively solve the problem of insufficient strength in the early stage, and the production cost of sulfur aluminate cement clinker is high and the setting time is difficult to control, which hinders the promotion and application of low-carb cement technology.
Using low-calcium silicate cement clinker, silicon-aluminum additive and composite treatment agent (sodium tetrapolypropylene benzenesulfonate, triisopropanolamine and water), the low-modification is prepared by efficient grinding and calcining technology. Carbocement improves the specific surface area and early strength of cement, and at the same time utilizes resources such as desert sand and coal gangue to reduce production costs.
It has achieved both early and late strength of cement, significantly reduced the water consumption of standard consistency, improved grinding efficiency, solved the waste of desert sand resources, and has significant economic and environmental benefits, which are suitable for promotion and application.
Smart Images

Figure GHA0000008263100000071 
Figure GHA0000008263100000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a modified low-carbon cement and a preparation method thereof. Background Art
[0002] Portland cement is usually first calcined from calcium, silicon, aluminum, and iron raw materials to form clinker, and then ground with appropriate amounts of mixed materials and gypsum; specifically, C3S accounts for about 37-67% of the clinker, C2S accounts for about 15-30%, C4AF accounts for about 10-18%, and C3A accounts for about 7-15%. The maximum temperature required to form C3S when calcining clinker is about 1450°C, and the temperature required for C2S to begin to form is only about 800°C, and the maximum content value is reached at 1100-1200°C. Such a clinker system causes the traditional cement production process to consume a large amount of resources such as limestone and coal, resulting in high carbon emissions. Therefore, the development of low-carbon cement is an urgent task, and reducing the proportion of C3S in the clinker system is one of the most direct and effective ways to prepare low-carbon cement.
[0003] Some studies have adopted the method of "reducing the calcium-silicon ratio in the clinker system" to reduce the proportion of C3S in cement clinker, while increasing the proportion of C2S to prepare high-belite cement; this cement has low carbon properties, and its clinker is still within the silicate system, but it usually has problems such as low early strength. Cement strength comes from the hydration products of the four clinker minerals in cement. The different hydration rates of the four minerals determine the different contribution rates of each mineral to the early and later strength of cement. The early strength of cement is mainly provided by the hydration reaction of C3S and C3A, and the later strength is mainly provided by the hydration reaction of C2S and C4AF. The proportion of C2S in high-belite cement is higher than that of C3S, resulting in insufficient early strength of the cement. Although the later strength is not greatly affected, the too low early strength delays the construction demolding time and project progress.
[0004] In response to the above problems, some studies have added sulphoaluminate cement clinker mineral components with faster hydration and hardening speed to high belite cement, thereby forming a belite-sulphoaluminate composite clinker system to shorten the early setting time of high belite cement and increase its hardening rate. However, the production cost of sulphoaluminate cement clinker is relatively high, and its rapid hardening characteristics require a high control accuracy of the setting time. After cooperating with high belite cement, it still faces new construction technical problems such as difficult to control the setting time. The promotion and application of existing "low-carbon" cement technology still faces many obstacles. Summary of the invention
[0005] The main purpose of the present invention is to provide a modified low-carbon cement in view of the problems and shortcomings of the prior art, which can make large-scale use of idle resources such as industrial solid waste and desert sand while ensuring the early and late strength of cement, and has significant economic and environmental benefits.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A modified low-carbon cement, wherein the components and their weight proportions include: 350-400 parts of low-calcium silicate cement clinker, 520-600 parts of silicoaluminate additive, 45-60 parts of desulfurized gypsum, and 5-20 parts of composite treatment agent; the composite treatment agent is composited with sodium tetrapropylene benzene sulfonate, triisopropanolamine and water as main raw materials.
[0008] In the above scheme, the mineral components and their mass percentages in the low-calcium silicate cement clinker include: C3S 11-30%, C2S 40-65%, C3A 4-10%, and C4AF 9-15%.
[0009] Preferably, the mineral components and their mass percentages in the low-calcium silicate cement clinker include: C3S 19-24%, C2S 52-58%, C3A 4-5%, and C4AF 14-15%.
[0010] Furthermore, the CaO content in the low-calcium silicate cement clinker is 58-60.5%.
[0011] In the above scheme, the low-calcium silicate cement clinker is obtained by drying, grinding, homogenizing and calcining limestone, clay and iron ore powder as main raw materials.
[0012] Furthermore, when the main raw material of low-calcium silicate cement clinker cannot meet the design requirements of the mineral composition ratio, coal gangue is added as a correction raw material.
[0013] In the above scheme, the raw materials of the low-calcium silicate cement clinker and their mass percentages include: limestone 75-78%, clay 18-21%; iron ore powder 1.7-4.5%, and coal gangue 0.00-1.75%.
[0014] In the above scheme, during the preparation of low-calcium silicate cement clinker, each raw material needs to be dried first, then ground to a fineness of 13-18% on a 0.08 mm square hole sieve, and each dry powder is weighed according to the ratio to form a raw meal, which is fed into a mixer for homogenization. The mixer fully mixes the raw meal during rotation, the mixer speed is 30-45 r / min, the homogenization time is 3-5 min, and finally the raw meal is fed into a calcining device for calcination, the maximum calcination temperature is 1300-1400°C, the heating rate is 10-12°C / min, and the insulation time after reaching the maximum calcination temperature is 30-60 min.
[0015] In the above scheme, the grinding can be carried out using an SM-500 cement test mill to achieve efficient grinding, and the grinding time is 20 to 30 minutes.
[0016] In the above scheme, the composite treatment agent is obtained by ultrasonic stirring with sodium tetrapropylene benzene sulfonate, triisopropanolamine and water as main raw materials, wherein the ultrasonic frequency used is 50-60KHz, the stirring rate is 600-800r / min, and the time is 12-14min.
[0017] In the above scheme, the raw materials in the composite treatment agent and their weight proportions include: 50-80 parts of sodium tetrapropylene benzene sulfonate, 10-20 parts of triisopropanolamine, and 10-40 parts of water.
[0018] In the above scheme, the silicon-aluminum additive is composited from desert sand and coal gangue.
[0019] Furthermore, the desert sand has a particle size of 110 to 280 μm, an average particle size of 150 to 260 μm, and does not need to be crushed before grinding, and has a SiO2 content of 73 to 77 wt%; the gangue is in blocky particles with a particle size of less than 7 mm, a SiO2 content of 52 to 55 wt%, and an Al2O3 content of 21 to 24 wt%.
[0020] In the above scheme, the mass ratio of the desert sand to the coal gangue is (1-4):1; it contributes additional active silicon dioxide and aluminum oxide to the system, participates in the secondary hydration reaction, and can be used as a filler for adjusting the particle grading.
[0021] The above-mentioned method for preparing a modified low-carbon cement comprises the following steps:
[0022] 1) Weigh the raw materials according to the proportion, and the raw materials and their mass percentages include: 350-400 parts of low-calcium silicate cement clinker, 520-600 parts of silicon-aluminum additive, 45-60 parts of desulfurized gypsum, and 5-20 parts of composite treatment agent;
[0023] 2) The weighed low-calcium silicate cement clinker, silicon-alumina additive and desulfurized gypsum are added into a mixer for homogenization, and then added into a cement test mill in the form of spraying, and the composite treatment agent is added for grinding; thus, the modified low-carbon cement is obtained.
[0024] In the above scheme, the mixing speed adopted in the homogenization step is 30-45 r / min, and the homogenization time is 3-5 min.
[0025] In the above scheme, the grinding speed adopted in the grinding step is 45-50r / min, and the grinding time is 20-30min.
[0026] Each solid component can be efficiently ground in the liquid composite treatment agent environment, and the specific surface area of the modified low-carbon cement formed is 540-560m 2 / kg, and at the same time can effectively reduce the water consumption of standard consistency, while taking into account good early strength, etc., the strength grade is above 52.5MPa.
[0027] The principle of the present invention is:
[0028] The invention firstly introduces a composite treatment agent with the functions of grinding aid, activation, modification and the like into low-calcium silicate cement clinker, and simultaneously adds a mineral additive rich in silicon and aluminum, and performs efficient grinding to obtain cement powder with high dispersibility. On the basis of effectively improving the specific surface area, the cement viscosity is reduced, and good mechanical properties (especially early strength, etc.) are taken into consideration at the same time: the triisopropanolamine solution is an oily liquid with a large viscosity, which is not conducive to uniform mixing with materials. The invention adopts sodium tetrapropylene benzene sulfonate as a salt solution to emulsify the triisopropanolamine, and the two achieve synergistic effect, greatly improve the grinding efficiency under the premise of achieving a high specific surface area, and at the same time, the sodium tetrapropylene benzene sulfonate can form a "thin shell" on the surface of the clinker to separate cement particles, so that the cement will not agglomerate after meeting water. Triisopropanolamine is an organic surfactant, which can reduce the surface energy of the mixture and achieve the purpose of aiding grinding. However, triisopropanolamine is an oily liquid after being dissolved in water, and the surface tension of triisopropanolamine is very different from that of water, which can easily cause the triisopropanolamine solution to be too viscous. In the grinding process, the viscous triisopropanolamine solution is not easy to disperse, and cement clinker, silicon-aluminum additives, and desulfurized gypsum are not easy to tend to a suspended state in the triisopropanolamine solution. It is easy for the material to be in a "cake-like" or "block-like" state due to excessive local contact with the triisopropanolamine solution. Therefore, the grinding aid effect of using a single triisopropanolamine is limited. The present invention is based on triisopropanolamine. Further compounding with sodium tetrapropylene benzene sulfonate can emulsify triisopropanolamine and achieve synergistic grinding aid effect, which significantly promotes the improvement of grinding aid effect; in addition, the sodium ions in the introduced sodium tetrapropylene benzene sulfonate can be exchanged with the calcium ions in the clinker, which is beneficial to promote a "thin shell" structure covering the surface of the clinker. This structure isolates the cement particles from each other, thereby ensuring that the cement with a high specific surface area after efficient grinding is still not easy to agglomerate after mixing with water, and can still maintain a low standard consistency water consumption; the synergistic effect of triisopropanolamine and sodium tetrapropylene benzene sulfonate can balance the contradiction between high specific surface area and low standard viscosity, and achieve excellent comprehensive effect.
[0029] The modified low-carbon cement obtained by the present invention not only follows the low-calcium carbon reduction concept, but also ensures that the early and late strengths of cement are equal to or even higher than those of traditional cement. At the same time, it can make full use of idle resources such as solid waste and desert sand, and has significant economic and environmental benefits.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) The composite treatment agent introduced in the present invention can realize the efficient grinding of low-calcium silicate cement clinker, silicon-alumina additives, etc. The obtained powder still has high dispersibility after contacting water, and effectively reduces the water consumption of standard consistency while increasing the specific surface area of cement and the activity of clinker;
[0032] 2) The silicon-aluminum additive used in the present invention is composed of desert sand and coal gangue, which can effectively solve the problem that desert sand cannot be used as construction sand due to round particles, too fine particle size, poor grading, etc., resulting in waste of resources, and can provide a new idea for the resource utilization of desert sand, coal gangue, etc.;
[0033] 3) The preparation method of the present invention is simple, easy to operate, has low preparation cost, is environmentally friendly, and is suitable for promotion and application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] In the following examples, the chemical compositions of limestone, clay, iron ore powder and coal gangue used are shown in Table 1;
[0036] Table 1 Chemical composition of raw materials (%)
[0037] name Loss on ignition <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO limestone 38.75 2.42 0.31 0.19 53.13 0.57 Clay 5.27 70.25 14.72 5.48 1.41 0.92 Iron ore powder / 34.42 11.53 48.27 3.53 0.09 Coal Gangue 16.67 52.37 22.23 3.77 1.76 0.32
[0038] The particle size of the desert sand used is mainly distributed between 110 and 280 μm, with an average particle size of 150 to 260 μm. It does not need to be crushed before grinding, and the SiO2 mass fraction is 73 to 77%. The coal gangue is in blocky particles with a particle size between 3 and 7 cm. It needs to be crushed to a particle size of less than 7 mm before grinding.
[0039] Example 1
[0040] A modified low-carbon cement, the preparation method of which comprises the following steps:
[0041] 1) Preparation of low calcium silicate cement clinker;
[0042] According to the low-calcium silicate cement clinker system, the three rates of clinker are designed to be KH=0.74, SM=2.94, and IM=1.74. Combined with the chemical composition of the raw materials limestone, clay, iron ore powder, and coal gangue used in this patent (see Table 1), the raw material mass ratio (%) is designed to be: limestone 77.34%, clay 19.22%, iron ore powder 1.72%, and coal gangue 1.72%. According to the raw material ratio, weigh the stone powder that has been ground to a fineness of (15±2)% on a 0.08 mm square hole sieve. Raw materials such as limestone, clay, and iron ore powder are homogenized in a mixer for 4 minutes (mixer speed is 30r / min), calcined at a maximum temperature of 1400°C (heating rate is 10°C / min) to partially melt and form clinker, and then cooled after keeping the temperature for 30 minutes to obtain low-calcium silicate cement clinker, in which the contents of C3S, C2S, C3A, and C4AF are 19.10%, 55.98%, 8.92%, and 9.26% respectively; the content of CaO is 60.32%;
[0043] 2) Preparation of composite treatment agent;
[0044] Weigh 50 parts (by weight, the same below) of sodium tetrapropylene benzene sulfonate powder and 10 parts of triisopropanolamine powder, mix the two with 40 parts of water, and subject the mixed solution to ultrasonic coordinated mechanical stirring for 12 minutes, wherein the mechanical stirring rate is 600r / min and the ultrasonic frequency is 50KHz, to obtain a composite treatment agent;
[0045] 3) Preparation of silicon-aluminum additives;
[0046] The desert sand and coal gangue are mixed evenly in a mass ratio of 1:1 to form a silicon-aluminum additive;
[0047] 4) Efficient grinding of each component
[0048] 350 parts of low-calcium silicate cement clinker, 600 parts of silicon-aluminum additives, and 45 parts of desulfurized gypsum were weighed, mixed evenly, and put into a cement test mill. Then, 5 parts of a composite treatment agent were added in a spraying form, and the mixture was ground at a mill speed of 48 r / min for 25 minutes to obtain the modified low-carbon cement.
[0049] Example 2
[0050] A modified low-carbon cement, the preparation method of which comprises the following steps:
[0051] 1) Preparation of low calcium silicate cement clinker;
[0052] According to the low-calcium silicate cement clinker system, the three ratios of clinker are designed to be KH=0.75, SM=2.53, and IM=1.14. Combined with the chemical composition of the raw materials limestone, clay, iron ore powder, and coal gangue used in this patent (see Table 1), the raw material mass ratio (%) is designed to be: limestone 77.22%, clay 18.94%, iron ore powder 3.84, and coal gangue 0%. According to the raw material ratio, weigh the limestone that has been ground to a fineness of (15±2)% on a 0.08 mm square hole sieve. , clay, iron ore powder and other raw materials are homogenized in a mixer for 4 minutes (mixer speed is 30r / min), calcined at a maximum temperature of 1350℃ (heating rate is 10℃ / min) to partially melt and form clinker, and then cooled after keeping the temperature for 30 minutes to obtain low-calcium silicate cement clinker, in which the contents of C3S, C2S, C3A and C4AF are 22.56%, 51.52%, 5.88% and 13.38% respectively; the content of CaO is 59.97%;
[0053] 2) Preparation of composite treatment agent;
[0054] Weigh 60 parts of sodium tetrapropylene benzene sulfonate powder and 20 parts of triisopropanolamine powder, mix the two with 20 parts of water, and subject the mixed solution to ultrasonic and mechanical stirring for 14 minutes, wherein the mechanical stirring rate is 700 r / min and the ultrasonic frequency is 60 KHz, to obtain a composite treatment agent;
[0055] 3) Preparation of silicon-aluminum additives;
[0056] The desert sand and coal gangue are mixed evenly in a mass ratio of 2:1 to form a silicon-aluminum additive;
[0057] 4) Efficient grinding of each component
[0058] 365 parts of low-calcium silicate cement clinker, 575 parts of silicon-aluminum additives, and 50 parts of desulfurized gypsum were weighed, mixed evenly, and put into a cement test mill. Then 10 parts of a composite treatment agent were added in a spraying form, and the mixture was ground at a mill speed of 48 r / min for 20 minutes to obtain the modified low-carbon cement.
[0059] Example 3
[0060] A modified low-carbon cement, the preparation method of which comprises the following steps:
[0061] 1) Preparation of low calcium silicate cement clinker;
[0062] According to the low-calcium silicate cement clinker system, the three rates of clinker are designed to be KH=0.73, SM=2.54, and IM=1.15. Combined with the chemical composition of the raw materials limestone, clay, iron ore powder, and coal gangue used in this patent, the raw material mass ratio (%) is designed to be: limestone 76.82%, clay 19.33%, iron ore powder 3.85%, and coal gangue 0%; according to the raw material ratio, limestone, clay, and iron ore powder that have been ground to a fineness of (15±2)% on a 0.08mm square hole sieve are weighed. The raw materials such as soil and iron ore powder are homogenized in a mixer for 4 minutes (mixer speed is 30r / min), calcined at a maximum temperature of 1350℃ (heating rate is 10℃ / min) to partially melt and form clinker, and then cooled after keeping the temperature for 30 minutes to obtain low-calcium silicate cement clinker, in which the contents of C3S, C2S, C3A and C4AF are 17.76%, 56.13%, 6.03% and 13.46% respectively; the content of CaO is 59.56%;
[0063] 2) Preparation of composite treatment agent
[0064] Weigh 70 parts of sodium tetrapropylene benzene sulfonate powder and 20 parts of triisopropanolamine powder, mix the two with 10 parts of water, and subject the mixed solution to ultrasonic and mechanical stirring for 14 minutes, wherein the mechanical stirring rate is 800 r / min and the ultrasonic frequency is 60 KHz, to obtain a composite treatment agent;
[0065] 3) Preparation of silicon-aluminum additives;
[0066] The desert sand and coal gangue are mixed evenly in a mass ratio of 3:1 to form a silicon-aluminum additive;
[0067] 4) Efficient grinding of each component
[0068] 380 parts of low-calcium silicate cement clinker, 545 parts of silicon-aluminum additives, and 55 parts of desulfurized gypsum were weighed, mixed evenly, and put into a cement test mill, and then 15 parts of a composite treatment agent were added in a spraying form, and ground at a mill speed of 48 r / min for 25 minutes to obtain the modified low-carbon cement.
[0069] Example 4
[0070] A modified low-carbon cement, the preparation method of which comprises the following steps:
[0071] 1) Preparation of low calcium silicate cement clinker;
[0072] According to the low-calcium silicate cement clinker system, the three rates of clinker are designed to be KH=0.71, SM=2.58, and IM=1.19. Combined with the chemical composition of the raw materials limestone, clay, iron ore powder, and coal gangue used in this patent, the raw material mass ratio (%) is designed to be: limestone 75.48%, clay 20.36%, iron ore powder 4.16%, and coal gangue 0%; according to the raw material ratio, limestone, clay, and iron ore powder that have been ground to a fineness of (15±2)% on a 0.08 mm square hole sieve are weighed. The raw materials such as soil and iron ore powder are homogenized in a mixer for 4 minutes (mixer speed is 30r / min), calcined at a maximum temperature of 1300℃ (heating rate is 10℃ / min) to partially melt and form clinker, and then cooled after keeping the temperature for 30 minutes to obtain low-calcium silicate cement clinker, in which the contents of C3S, C2S, C3A and C4AF are 11.97%, 61.44%, 6.33% and 13.21% respectively; the content of CaO is 58.83%;
[0073] 2) Preparation of composite treatment agent
[0074] Weigh 80 parts of sodium tetrapropylene benzene sulfonate powder and 10 parts of triisopropanolamine powder, mix the two with 10 parts of water, and subject the mixed solution to ultrasonic and mechanical stirring for 14 minutes, wherein the mechanical stirring rate is 800r / min and the ultrasonic frequency is 60KHz, to obtain a composite treatment agent;
[0075] 3) Preparation of silicon-aluminum additives;
[0076] The desert sand and coal gangue are mixed evenly in a mass ratio of 4:1 to form a silicon-aluminum additive;
[0077] 4) Efficient grinding of each component
[0078] 400 parts of low-calcium silicate cement clinker, 520 parts of silicon-aluminum additives, and 60 parts of desulfurized gypsum were weighed, mixed evenly, and put into a cement test mill, and then 20 parts of a composite treatment agent were added in a spraying form, and ground at a mill speed of 48 r / min for 30 minutes to obtain the modified low-carbon cement.
[0079] Comparative Example 1
[0080] A modified low-carbon cement, the preparation method of which is substantially the same as that of Example 3, except that:
[0081] 1) The preparation steps of the composite treatment agent include: weighing 20 parts of triisopropanolamine powder and mixing it with 80 parts of water, and subjecting the mixture to ultrasonic and mechanical stirring for 14 minutes, wherein the mechanical stirring rate used is 800r / min and the ultrasonic frequency is 60KHz;
[0082] 2) The raw materials in cement and their weight proportions are: 380 parts of low-calcium silicate cement clinker, 545 parts of silicon-aluminum additive, 55 parts of desulfurized gypsum, and 25 parts of composite treatment agent.
[0083] Comparative Example 2
[0084] A modified low-carbon cement, the preparation method of which is substantially the same as that of comparative example 1, except that the grinding time adopted in step 4) is 60 minutes.
[0085] Comparative Example 3
[0086] A modified low-carbon cement, the preparation method of which is substantially the same as that of Example 3, except that:
[0087] Step 1) The preparation step of the composite treatment agent includes: weighing 70 parts of sodium tetrapropylene benzene sulfonate powder and mixing it with 30 parts of water, and subjecting the mixture to ultrasonic and mechanical stirring for 14 minutes, wherein the mechanical stirring rate used is 800r / min and the ultrasonic frequency is 60KHz.
[0088] Comparative Example 4
[0089] A modified low-carbon cement, the preparation method of which is substantially the same as that of Example 3, except that:
[0090] In step 1) of preparing the composite treatment agent, the raw materials used and their weight proportions are: 20 parts of sodium tetrapropylene benzene sulfonate powder, 70 parts of triisopropanolamine powder and 10 parts of water.
[0091] The cements obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for performance, and the results are shown in Table 2.
[0092] Table 2 Performance test results of cement obtained from Examples 1 to 4 and Comparative Examples 1 to 4
[0093]
[0094]
[0095] Note: ① The comprehensive carbon emissions are the sum of the carbon emissions generated by the three links of limestone decomposition in clinker, clinker calcination and cement grinding. The calculation formula is: Comprehensive carbon emissions = limestone consumption * 44 / 100 + calcination time in high-temperature furnace * 27 / 60 + grinding time * 2.2 * 0.68 / 60.
[0096] ② In order to better reflect the low-carbon properties of the cement, the calculation method of the present invention is used to calculate the comprehensive carbon emissions of P.O52.5R cement, and the contents of its clinker mineral components C3S, C2S, C3A, and C4AF are set to 55%, 25%, 9%, and 11%, respectively. It is calcined in a high-temperature furnace with a maximum temperature of 1450°C.
[0097] By analyzing the data in the above table, it can be seen that in Comparative Examples 1 and 2 where sodium tetrapropylene benzene sulfonate is not added, the compressive strength of cement mortar at each age is greatly reduced compared with Examples 1-4, among which Comparative Example 1 has the largest reduction. Although its grinding time is the same as that of Example 3 and the converted amount of triisopropanolamine is the largest, the specific surface area is still greatly reduced, which is only 368m 2 / kg, resulting in the early hydration activity of high belite cement still being at a low level, the setting time is greatly delayed, the initial setting time is 350min, the final setting time is 400min, the standard viscosity is greatly improved than Example 1-4, which is 26.9%, and the 3d compressive strength is only 13.8MPa, which seriously affects the construction demoulding and progress. Although the comprehensive carbon emissions of cement in Example 1-2 are within the range of the comprehensive carbon emissions of Example 3-4, the setting time and mechanical properties of the former are far inferior to those of the latter. Comparative Example 1 maintains the same grinding time as Example 3, but the specific surface area of cement in Comparative Example 1 is much lower than that in Example 3; while Comparative Example 2 maintains a similar specific surface area as Example 3, but the grinding time of cement in Comparative Example 2 is much longer than that of cement in Example 3. The reason for the above phenomenon is that in Comparative Example 1-2, C2S is more difficult to grind than C3S. High C2S content will increase the difficulty of cement grinding and prolong the grinding time. In addition, the hydration activity of C2S is lower than that of C3S, the early activity of cement decreases, the setting time is prolonged, and the 3d-28d compressive strength decreases accordingly. In Comparative Example 2, the carbon emission of cement grinding increases, resulting in a slightly higher comprehensive carbon emission than that of Comparative Example 1.
[0098] By comparing Examples 1-4, it can be seen that as the C2S content gradually increases and the C3S content gradually decreases, when sodium tetrapropylene benzene sulfonate is present in the composite treatment agent as a "thin shell" material and dispersant and triisopropanolamine are used as grinding aid components, the cement test mill contacts, collides and reacts with each other during the efficient grinding process, which is conducive to promoting the reaction between sodium tetrapropylene benzene sulfonate and the surface of cement clinker to form a "thin shell" wrapped on the surface of cement clinker particles, so that the cement clinker particles are alienated from each other. Under the high specific surface area characteristics brought about by efficient grinding, cement is still not easy to agglomerate after adding water, and high dispersibility is maintained, so that the standard viscosity of cement is maintained in the range of 17.2-19.4%, which is lower than the standard viscosity in Comparative Examples 1-2; on the other hand, the high specific surface area brought about by efficient grinding improves the hydration activity of cement clinker, ensuring that the cement strength at different ages is greatly improved compared with Comparative Examples 1-2, overcoming the problem of insufficient early strength of high belite cement. Among them, the more optimal formula is the range of each component between Examples 2-3. The strength of Example 4 is lower than that of Example 3 because the C2S content has exceeded the optimal limit at this time. Even if the specific surface area of the cement particles wrapped in the upper thin shell remains unchanged after efficient grinding, the mechanical activation of C2S has reached its limit, and the strength provided by the mineral components is still lower than that of Example 3. The comprehensive carbon emissions of cement in Examples 1-4 are significantly lower than that of PO 52.5R, indicating that they have low-carbon properties.
[0099] Comparison of Comparative Example 3 with Example 3 shows that pure sodium tetrapropylene benzene sulfonate will also lead to a decrease in grinding efficiency. Under the premise that the grinding time is 25 min, the specific surface area of Comparative Example 3 is only 350 m 2 / kg, which is about 38% lower than that in Example 3. It can be seen from Comparative Example 1 and Example 3 that in the absence of sodium tetrapropylene benzene sulfonate, triisopropanolamine as a single-component grinding aid only plays a conventional grinding aid role. In addition, it can be seen from Comparative Example 1 and Comparative Example 3 that the specific surface areas of the two are relatively close and both are relatively low. Further, it can be seen from Comparative Example 4 and Example 3 that the composite system with high sodium tetrapropylene benzene sulfonate content can effectively ensure efficient grinding and good activation and modification effects.
[0100] In summary, the present invention uses sodium tetrapropylene benzene sulfonate and triisopropanolamine in combination, and the synergistic effect of the two greatly improves the grinding efficiency; at the same time, it has high dispersibility during the efficient grinding process, and the sodium tetrapropylene benzene sulfonate in the composite treatment agent reacts with the calcium ions on the surface of the low-calcium silicate cement clinker particles, and a "thin shell" is formed on the clinker surface, and its chemical composition is calcium tetrapropylene benzene sulfonate; the synergistic effect of triisopropanolamine and sodium tetrapropylene benzene sulfonate can balance the contradiction between high specific surface area and low standard viscosity. The cement obtained by the present invention has a large specific surface area, improved clinker activity, and the standard consistency water consumption remains unchanged or even decreases compared with traditional silicate cement, and its mechanical properties are comparable to or even higher than those of traditional silicate cement, and has excellent low-carbon properties.
[0101] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A modified low carbon cement, characterized in that: The components and their weight proportions include: 350-400 parts of low-calcium silicate cement clinker, 520-600 parts of silicoaluminate additive, 45-60 parts of desulfurized gypsum, and 5-20 parts of composite treatment agent; the composite treatment agent is composited with sodium tetrapropylene benzene sulfonate, triisopropanolamine and water as main raw materials.
2. The modified low carbon cement according to claim 1, characterized in that: The mineral components and their mass percentages in the low-calcium silicate cement clinker include: C3S 11-30%, C2S 40-65%, C3A 4-10%, and C4AF 9-15%.
3. The modified low carbon cement according to claim 1, characterized in that: The low-calcium silicate cement clinker is obtained by taking limestone, clay and iron ore powder as main raw materials through drying, grinding, homogenizing and calcining.
4. The modified low carbon cement according to claim 1, characterized in that: The raw materials of the low-calcium silicate cement clinker and their mass percentages include: limestone 75-78%; clay 18-21%; iron ore powder 1.7-4.5%; coal gangue 0.00-1.75%.
5. The modified low carbon cement according to claim 1, characterized in that: The composite treatment agent is obtained by ultrasonically stirring tetrapropylene sodium benzene sulfonate, triisopropanolamine and water as main raw materials.
6. The modified low carbon cement according to claim 5, characterized in that: The raw materials in the composite treatment agent and their weight proportions include: 50-80 parts of sodium tetrapropylene benzene sulfonate, 10-20 parts of triisopropanolamine, and 10-40 parts of water.
7. The modified low carbon cement according to claim 1, characterized in that: The silicon-aluminum additive is composited from desert sand and coal gangue.
8. The modified low carbon cement according to claim 7, characterized in that: The desert sand has a particle size of 110 to 280 μm, an average particle size of 150 to 260 μm, and does not need to be crushed before grinding. The SiO2 content is 73 to 77 wt%; the coal gangue is in blocky particles with a particle size of less than 7 mm, a SiO2 content of 52 to 55 wt%, and an Al2O3 content of 21 to 24 wt%.
9. The method for preparing the modified low carbon cement according to any one of claims 1 to 8, characterized in that: The steps include: 1) Weigh the raw materials according to the proportion, and the raw materials and their mass percentages include: 350-400 parts of low-calcium silicate cement clinker, 520-600 parts of silicon-aluminum additive, 45-60 parts of desulfurized gypsum, and 5-20 parts of composite treatment agent; 2) The weighed low-calcium silicate cement clinker, silicon-alumina additive and desulfurized gypsum are added into a mixer for homogenization, and then added into a cement test mill in the form of spraying, and the composite treatment agent is added for grinding; thus, the modified low-carbon cement is obtained.
10. The preparation method according to claim 9, characterized in that The grinding time is 20 to 30 minutes.
Citation Information
Patent Citations
Cement grinding aid and preparation method thereof
CN101125742A
Low-calcium silicate cement clinker prepared from high-aluminum limestone and preparation method thereof
CN108821618A